2015
DOI: 10.1016/j.jtcvs.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four contemporary risk models at predicting mortality after aortic valve replacement

Abstract: All 4 risk scores discriminated operative mortality after isolated AVR. The EuroSCORE had poor calibration, overestimating operative mortality, although the other 3 scores fitted well with contemporary outcomes. The STS score was the best calibrated in the highest quintile of operative risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…In terms of calibration, we found the original EuroSCORE to over‐estimate operative mortality by about three times, compared to the two more contemporary scores similar to other studies . The only other study reporting calibration of risk scores for MVR found that both EuroSCORE II and STS Score also significantly over‐estimated operative mortality by 2‐3 times; however, in this cohort operative mortality was relatively low at only 1.0% .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In terms of calibration, we found the original EuroSCORE to over‐estimate operative mortality by about three times, compared to the two more contemporary scores similar to other studies . The only other study reporting calibration of risk scores for MVR found that both EuroSCORE II and STS Score also significantly over‐estimated operative mortality by 2‐3 times; however, in this cohort operative mortality was relatively low at only 1.0% .…”
Section: Discussionsupporting
confidence: 79%
“…Compared to studies of other types of cardiac surgery from our center, discrimination of risk scores was best in MVR. C‐statistics were lowest 0.64‐0.68 for isolated coronary bypass grafting, higher 0.71‐0.75 for isolated aortic valve replacement, and 0.59‐0.70 for the combined procedure for the same three risk scores . This is somewhat surprising for EuroSCORE and EuroSCORE II which were derived from populations predominantly made up of those undergoing coronary surgery.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Euroscore II had better predictive discrimination for operative mortality than Euroscore I and is comparable to the STS risk score [3]. This may be due to the inclusive nature of Euroscore II for many procedures that make it more flexible than the STS score for complex procedures.…”
Section: Discussionmentioning
confidence: 92%
“…Several risk stratification scores (Euroscore I, Euroscore II, Society of thoracic surgery (STS) score, and the Australian model) were compared to predict the operative mortality after isolated AVR [3]. The Euroscore I had a poor calibration value and overestimated the mortality; however; the other scores correlated well with the outcome, and the highest accuracy was reported with STS score [3][4][5]. Other studies found that the Euroscore II was as effective as the STS risk score in predicting operative mortality [6].…”
mentioning
confidence: 99%